Hāfizūn and Yaktumūn: Ethical Foundations for the Preservation of and Access to Cultural Heritage in GLAM Institutions - Vita Amelia; Abdul Mustaqim (Institut Agama Islam Negeri (IAIN) Curup, 2026)
GLAM institutions (Galleries, Libraries, Archives, and Museums) face an ethical tension between preserving cultural heritage and providing public access to it. Strict preservation practices may produce restrictive access regimes, while uncontrolled access risks damaging collections. This study aims to formulate an ethical framework to address this tension, constructed from QS. Al-Hijr [15]:9 and QS. Al-Baqarah [2]:159 through interpretation. Using Qualitative library research and thematic interpretation, this article analyzes two key concepts: the custodial mission (Hāfizūn) in QS. Al-Hijr: 9 and the prohibition of concealing knowledge (Yaktumūn) in QS. Al-Baqarah: 159. The analysis shows that QS. Al-Hijr [15]:9 legitimizes preservation ethics, while QS. Al-Baqarah [2]:159 grounds ana ethnics accessibility. The synthesis yields an ethical model that integrates authenticity, integrity, equity, transparency, and controlled access as its core elements. The study offers theological-ethical guidance for GLAM policy and enriches Islamic information ethics, complementing existing secular approaches (Floridi’s information ethics, IFLA/ICA/UNESCO codes) with a theologically grounded perspective relevant to Muslim-majority contexts and to global discourse alike.